2016
DOI: 10.12693/aphyspola.130.1023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Boron Addition on the Structure of the Ni-Mn-Co-In Alloys

Abstract: Series of Ni45.5−xCo4.5Mn36.6In13.4Bx (at.%, x = 0, 0.05, 0.1, 0.5, 1.0) polycrystalline magnetic shape memory alloys produced by the induction melting were examined in terms of the structure and transition temperatures. The structure of the alloys was determined by the X-ray diffraction and transmission electron microscopy. Scanning electron microscopy and electron backscattering diffraction techniques were applied to obtain the microstructure and texture of alloys. Boron addition promotes nucleation of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The ductility of Ni-Mn-based alloys can be improved by doping the B element, introducing second-phase particles at grain boundaries. In 2011, Nong et al [ 61 ] studied Ni-Mn-Sb alloys with B doping and found that if the content of the B element was increased from 1 at.% to 3 at.%, the Curie temperature increased from 330 K to 345 K, and the martensitic transformation temperature decreased from 300 K to 262 K. Prusik et al [ 62 ] investigated the Ni-Mn-Co-In alloy doped with the B element and found that the B element facilitated the formation of “Co-rich and In-deficient” γ phase and M 23 B 6 phase. When the B content reached 1 at.%, the second phases formed a “sub grain “ structure within the grain interiors and at the grain boundaries.…”
Section: The Effects Of Doping On the Toughness Of Ni-mn-based Alloysmentioning
confidence: 99%
“…The ductility of Ni-Mn-based alloys can be improved by doping the B element, introducing second-phase particles at grain boundaries. In 2011, Nong et al [ 61 ] studied Ni-Mn-Sb alloys with B doping and found that if the content of the B element was increased from 1 at.% to 3 at.%, the Curie temperature increased from 330 K to 345 K, and the martensitic transformation temperature decreased from 300 K to 262 K. Prusik et al [ 62 ] investigated the Ni-Mn-Co-In alloy doped with the B element and found that the B element facilitated the formation of “Co-rich and In-deficient” γ phase and M 23 B 6 phase. When the B content reached 1 at.%, the second phases formed a “sub grain “ structure within the grain interiors and at the grain boundaries.…”
Section: The Effects Of Doping On the Toughness Of Ni-mn-based Alloysmentioning
confidence: 99%
“…That proves the L2 1 ordering. The space group of the matrix is F m3m and the lattice parameter a 0 = 5.98 Å [11]. The structure of the precipitates of B010-B100 alloys were determined as M 23 B 6 .…”
Section: Structure Of the Alloysmentioning
confidence: 99%